Fatty acid composition of raw milk samples from factories located in western part of Hungary - Viszket, Erna; Csavajda, Éva; Varga, László; Tanai, Attila; Tóth, Tamás (Acta Agraria Kaposváriensis, 2011)
The authors was evaluated protein, fat content and fatty acid composition of raw milk samples delivered to a cheese factory located in western part of Hungary in a 2-yearlong study. In accordance with literature data the highest contents of fat were measured in samples taken in winter (3.92%), while the lowest mean was observed in summer (3.64%). As for the protein contents of bulk milk samples, the highest mean (3.43%) was observed in fall, while the lowest one (3.17%) in summer. There was no significant year effect on fat content between the two sampling years, however significant differences (P=0.01) were proved in the protein content of milk samples. Season significantly influenced (P=0.05) the levels of saturated fatty acids (SFA) in milk, except the C17:0. As for monounsaturated fatty acids (MUFA), the highest mean (28.97%) was observed in summer. In the group of polyunsaturated fatty acids (PUFA), seasonal differences (P=0.05) were found only in linoleic acid (C18:2) and in eicosatrienoic acid (C20:3) levels. This study proved indirectly the season independent use of diets based on preserved fodder (e. g. maize silage). Besides obvious economic benefits of using preserved fodder based diets it is suggested that it would be preferable to apply feeding procedures in practice, which may improve the content of PUFAs in milk (especially the levels of omega-3 fatty acids and CLA). Application of new methods in feeding could have favourable effects not only on opening up new market opportunities but on the characteristics of some certain dairy products (e.g. improving spreadability of butter).
Keywords: raw milk; fat content; fatty acid profile; omega-3; CLA